2007
DOI: 10.1088/0965-0393/15/5/002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of van der Waals forces on increasing the strength and toughness in dynamic fracture of nanofibre networks: a peridynamic approach

Abstract: The peridynamic method is used here to analyse the effect of van der Waals forces on the mechanical behaviour and strength and toughness properties of three-dimensional nanofibre networks under imposed stretch deformation. The peridynamic formulation allows for a natural inclusion of long-range forces (such as van der Waals forces) by considering all interactions as 'long-range'. We use van der Waals interactions only between different fibres and do not need to model individual atoms. Fracture is introduced at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 41 publications
(96 reference statements)
0
67
0
Order By: Relevance
“…The method is particularly well suited for dealing with cracks and damage in solid mechanics (see [25,26]) especially in situations where the crack path, for example, is not known in advance. The method also allows for easy introduction of longrange forces, such as van der Waals interactions and examples of deformation and damage at the nanoscale are treated in [26,27]. In fact, all forces in the peridynamic formulation are long-range.…”
Section: Overview Of Peridynamicsmentioning
confidence: 99%
“…The method is particularly well suited for dealing with cracks and damage in solid mechanics (see [25,26]) especially in situations where the crack path, for example, is not known in advance. The method also allows for easy introduction of longrange forces, such as van der Waals interactions and examples of deformation and damage at the nanoscale are treated in [26,27]. In fact, all forces in the peridynamic formulation are long-range.…”
Section: Overview Of Peridynamicsmentioning
confidence: 99%
“…Regardless of the exact value of 未, the peridynamic equations retain their applicability on crack tips and surfaces. If it is additionally required to reproduce effects controlled by small-scale behavior, such as dispersion curves, then 未 must be chosen to reflect the relevant physical length scale [5][6][7]. An example of a physically determined length scale is the spacing of aggregate in concrete; Bazant has shown that a suitable nonlocal model for concrete has advantages over a homogenized local model in the prediction of damage and localization [8].…”
Section: Length Scales Nonlocality and Continuamentioning
confidence: 99%
“…Propagation, as opposed to nucleation, of cracks within the peridynamic model has been described elsewhere (Silling and Askari 2005) and has been applied to a number of problems involving complex patterns of fracture (Silling 2003;Silling and Bobaru 2005;Askari et al 2006;Bobaru 2007;Xu et al 2007;Colavito et al 2007;Gerstle et al 2007;Xu et al 2008;Agwai et al 2008a,b;Agwai et al 2009). Crack growth occurs through the irreversible breakage of bonds as they stretch in the vicinity of a crack tip.…”
Section: Introductionmentioning
confidence: 99%